TAF1 Transcripts and Neurofilament Light Chain as Biomarkers for X‐linked Dystonia‐Parkinsonism. Issue 1 (25th September 2020) - Al Ali, Jamal; Vaine, Christine A.; Shah, Shivangi; Campion, Lindsey; Hakoum, Ahmad; Supnet, Melanie L.; Acuña, Patrick; Aldykiewicz, Gabrielle; Multhaupt‐Buell, Trisha; Ganza, Niecy G.M.; Lagarde, John B.B.; De Guzman, Jan K.; et al.
ABSTRACT: Background: X‐linked dystonia‐parkinsonism is a rare neurological disease endemic to the Philippines. Dystonic symptoms appear in males at the mean age of 40 years and progress to parkinsonism with degenerative pathology in the striatum. A retrotransposon inserted in intron 32 of the TAF1 gene leads to alternative splicing in the region and a reduction of the full‐length mRNA transcript. Objectives: The objective of this study was to discover cell‐based and biofluid‐based biomarkers for X‐linked dystonia‐parkinsonism. Methods: RNA from patient‐derived neural progenitor cells and their secreted extracellular vesicles were used to screen for dysregulation of TAF1 expression. Droplet‐digital polymerase chain reaction was used to quantify the expression of TAF1 mRNA fragments 5′ and 3′ to the retrotransposon insertion and the disease‐specific splice variant TAF1‐32i in whole‐blood RNA. Plasma levels of neurofilament light chain were measured using single‐molecule array. Results: In neural progenitor cells and their extracellular vesicles, we confirmed that the TAF1 ‐3′/5′ ratio was lower in patient samples, whereas TAF1 ‐32i expression is higher relative to controls. In whole‐blood RNA, both TAF1‐3′/5′ ratio and TAF1‐32i expression can differentiate patient (n = 44) from control samples (n = 18) with high accuracy. Neurofilament light chain plasma levels were significantly elevated in patients (n = 43) compared with both carriers (n = 16) and controls (n = 21), with area under the curve of 0.79. Conclusions: TAF1 dysregulation in blood serves as a disease‐specific biomarker that could be used as a readout for monitoring therapies targeting TAF1 splicing. Neurofilament light chain could be used in monitoring neurodegeneration and disease progression in patients. © 2020 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society.